2020
DOI: 10.1002/marc.202000477
|View full text |Cite
|
Sign up to set email alerts
|

Viability of Low Molecular Weight Lignin in Developing Thiol‐Ene Polymer Electrolytes with Balanced Thermomechanical and Conductive Properties

Abstract: Polymer electrolytes with high aromatic content are prepared through thiol‐ene polymerization with functionalized, low molecular weight fractions of softwood pine Kraft lignin, and wheat straw/Sarkanda grass soda lignin. Differing solubility, functionality, and aromatic content of the lignin fractions vary the glass transition temperatures of the resulting polymers and the suitability for electrolyte applications. The softwood pine Kraft lignin is used as a precursor for a gel polymer electrolyte (GPE) with ro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 43 publications
(54 reference statements)
0
6
0
Order By: Relevance
“…There are enormous aromatic ring structures and abundant polar groups in the lignin, such as phenolic hydroxyl, carboxyl, and methoxy groups on its side chains, which can easily cause excessive intermolecular forces, resulting in poor dispersibility in the material, which affects the conductivity. 22 Thus, as the amount of added lignin increases, the increased terminal groups lead to a decrease in the conductivity when the amount of added lignin is more than 0.1%. It is known that the PEO chains form a stable complex with cations; thus the change in the formation of interacted PEO units can be confirmed from the vibrational characterization.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…There are enormous aromatic ring structures and abundant polar groups in the lignin, such as phenolic hydroxyl, carboxyl, and methoxy groups on its side chains, which can easily cause excessive intermolecular forces, resulting in poor dispersibility in the material, which affects the conductivity. 22 Thus, as the amount of added lignin increases, the increased terminal groups lead to a decrease in the conductivity when the amount of added lignin is more than 0.1%. It is known that the PEO chains form a stable complex with cations; thus the change in the formation of interacted PEO units can be confirmed from the vibrational characterization.…”
mentioning
confidence: 99%
“…Although lignin has many outstanding properties, there are still limited studies on lignin as a functional additive applied to Li batteries, with it so far mostly being studied for use in anodes, 16,17 binders, 18,19 and gel electrolytes. [20][21][22] Moreover, the previous studies on electrolytes for batteries only focused on lignin that needs complex graft copolymerization. 23,24 Furthermore, all the applied lignin uses conventional extraction procedures, such as thermochemical treatment.…”
mentioning
confidence: 99%
“…Therefore, lignin fractions soluble in iPrOH can be used for the manufacturing of lignin-based epoxy resin where highly reactive lignins are required. Otherwise, these first fractions of lignin presented low molecular weight and low polydispersity index which can be utilised in the fabrication of polymer electrolytes (Baroncini et al, 2021).…”
Section: Applicability Of the Sequential Organic Solvent Extraction Methodsmentioning
confidence: 99%
“…Compared to lignin polymers, low-Mw lignin fractions contain more hydroxyl groups and reactive sites, which could enhance the accessibility of reaction sites and make the reaction more uniform. Using low-Mw lignin fractions can reduce dispersity and enhance reactivity by separating fractions based on their molecular weight. , Low-Mw lignin obtained by lignin fractionation is both more economical and practical than unfractionated lignin or lignin-derived monomers . Gioia et al reported the relationship between the lignin structural network and thermomechanical properties of lignin-based thermosetting epoxy resin prepared using the lignin fraction of spruce sulfate lignin with a relatively lower molecular weight (Mw) (∼1000 g mol –1 ) .…”
Section: Introductionmentioning
confidence: 99%
“…11,12 Low-Mw lignin obtained by lignin fractionation is both more economical and practical than unfractionated lignin or ligninderived monomers. 13 Gioia et al reported the relationship between the lignin structural network and thermomechanical properties of lignin-based thermosetting epoxy resin prepared using the lignin fraction of spruce sulfate lignin with a relatively lower molecular weight (Mw) (∼1000 g mol −1 ). 14 Jablonkis et al prepared high-viscosity lignin-based epoxy resins suitable for adhesives and crack fillers by glycidylation of acetone-soluble lignin fractions and employing a 10% substitution of BPA.…”
Section: ■ Introductionmentioning
confidence: 99%